Irrigation and Inclusiveness in Health: A Study of Two Villages in North East Karnataka. (July 2021) - Scaria, Suma
Does irrigation mediate inclusiveness in health outcomes? This is the basic question this article is trying to address in the context of two villages in northeast Karnataka. The findings of this micro-level study show that public irrigation facilitates trickle down of positive health outcomes to the marginalised sections of the society in terms of caste and gender. On the other hand, such inclusiveness in health was not observed in the village where majority of households depend on private sources of irrigation. The above outcomes are explained in terms of inequities in access to resources including water, land and education. This study shows that public irrigation plays instrumental role in achieving larger developmental goals including health in a rural society.